AGRICULTURA FAMILIAR E SUSTENTABILIDADE: O CULTIVO DE HORTALIÇAS EM MATEIROS; JALAPÃO (REMUNOM, 2025)
The article "Family Farming and Sustainability: Vegetable Cultivation in Mateiros, Jalapão" presents a detailed and sensitive approach to the importance of family farming for the economy, food security and environmental preservation in Jalapão. The appreciation of the work of farmers, especially women who lead sustainable production, enriches the narrative and highlights the strength of tradition combined with innovation in the field.